Dove's advertising campaign highs and lows : from real beauty to real success to real controversy - Brooks, Bradley; Chanland, Dawn; Cox, Steven (Steven M.) (London : Society for Case Research, 2020)
For years as Unilever’s brand director of skin cleansing, Jennifer Bremner, had enjoyed Dove’s tremendous brand success as it sought to redefine the definition of feminine beauty. A 2017 Dove body wash promotion, however, attracted more than mere attention-to the point of igniting a racial firestorm. Consumers expressed outrage against Dove with online accusations that the brand promoted racial hatred and bigotry. The brand was confronting calls for boycotts with es-calating consumer hostility and national media featured stories about the controversy that threatened the brand. Having been recently promoted based on her Dove brand leadership, Bremner mused over how the carefully built brand loyalty and sales might be damaged.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Product management -- Case studies; Advertising -- Soap -- Case studies